2015
DOI: 10.5665/sleep.4574
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Increased Risk of Autoimmune Diseases in Individuals without Sleep Apnea

Abstract: Patients with non-apnea sleep disorder were associated with a higher risk for developing autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 21 publications
2
69
0
Order By: Relevance
“…The demographic characteristics for all sampled participants are shown in Table , including 91 273 NSD patients and 91 273 controls. NSD included 45.58% of insomnia (ICD‐9‐CM codes: 780.52, 307.41, 307.42), 46.81% of sleep disturbance (ICD‐9 CM codes: 780.5, 780.50) and 7.62% of other disorders related to the sleep–wake schedule and parasomnias (ICD‐9 CM codes: 780.55, 780.56, 780.59 and 307.4) (Hsiao et al ., ). The controls were matched for age, gender, income, urbanization level and the CCI score (all P > 0.9).…”
Section: Resultsmentioning
confidence: 97%
“…The demographic characteristics for all sampled participants are shown in Table , including 91 273 NSD patients and 91 273 controls. NSD included 45.58% of insomnia (ICD‐9‐CM codes: 780.52, 307.41, 307.42), 46.81% of sleep disturbance (ICD‐9 CM codes: 780.5, 780.50) and 7.62% of other disorders related to the sleep–wake schedule and parasomnias (ICD‐9 CM codes: 780.55, 780.56, 780.59 and 307.4) (Hsiao et al ., ). The controls were matched for age, gender, income, urbanization level and the CCI score (all P > 0.9).…”
Section: Resultsmentioning
confidence: 97%
“…The presence of abnormal sleep for patients with Crohn's disease in remission at baseline has been linked with 2× increased risk of disease flare within the subsequent 6 months [ 14 ]. Two separate longitudinal studies found that individuals with sleep disorder [ 73 ] and patients with obstructive sleep apnoea [ 74 ] were at a higher risk for developing autoimmune diseases (including ankylosing spondylitis). It is therefore possible that regular screening for disturbed sleep could be useful in assessing disease activity and predicting future flares.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep has a strong regulatory influence on immune functions. The disturbance of the body's immunity caused by sleep deprivation is not limited to the suppression of the response to pathogens; it can also result in the collapse of immunological self-tolerance, which can cause the onset of autoimmune disease [1][2][3]. Cross-sectional studies have shown that sleep disorders in individuals with autoimmune diseases are correlated with pain, fatigue, psychiatric manifestations, and disease activity [4].…”
Section: Introductionmentioning
confidence: 99%